A Pleasing Odour for Yahweh. (14th June 2018) - de Hemmer Gudme, Anne Katrine
Abstract : This article investigates the importance of smell in the sacrificial cults of the ancient Mediterranean, using the Yahweh temple on Mount Gerizim and the Hebrew Bible as a case-study. The material shows that smell was an important factor in delineating sacred space in the ancient world and that the sense of smell was a crucial part of the conceptualization of the meeting between the human and the divine. In the Hebrew Bible, the temple cult is pervaded by smell. There is the sacred oil laced with spices and aromatics with which the sanctuary and the priests are anointed. There is the fragrant and luxurious incense, which is burnt every day in front of Yahweh and finally there are the sacrifices and offerings that are burnt on the altar as 'gifts of fire' and as 'pleasing odors' to Yahweh. The gifts that are given to Yahweh are explicitly described as pleasing to the deity's sense of smell. On Mount Gerizim, which is close to present-day Nablus on the west bank, there once stood a temple dedicated to the god Yahweh, whom we also know from the Hebrew Bible. The temple was in use from the Persian to the Hellenistic period (ca. 450 – 110 BCE) and during this time thousands of animals (mostly goats, sheep, pigeons and cows) were slaughtered and burnt on the altar as gifts to Yahweh. The worshippers who came to the sanctuary – and we know some of them by name because they left inscriptions commemorating their visit to the temple – would have experienced an overwhelming combination of smells: the smell of spicy herbs baked by the sun that is carried by the wind, the smell of humans standing close together and the smell of animals, of dung and blood, and behind it all as a backdrop of scent the constant smell of the sacrificial smoke that rises to the sky.